Adaptive partial policy innovation: Coping with ambiguity through diversification - Charles F. Manski (Centre for Microdata Methods and Practice (cemmap), 2008)
This paper develops a broad theme about policy choice under ambiguity through study of a particular decision criterion. The broad theme is that, where feasible, choice between a status quo policy and an innovation is better framed as selection of a treatment allocation than as a binary decision. Study of the static minimax-regret criterion and its adaptive extension substantiate the theme. When the optimal policy is ambiguous, the static minimax-regret allocation always is fractional absent large fixed costs or deontological considerations. In dynamic choice problems, the adaptive minimax-regret criterion treats each cohort as well as possible, given the knowledge available at the time, and maximizes intertemporal learning about treatment response.
Keywords: D7; H0; 330; Entscheidungstheorie; Politik; Präferenztheorie